Optimalisasi Proses Stabilisasi Lumpur Tekstil Dengan Semen - Dwinna Rahmi; sri pudji Rahayu; Sumingkrat Sumingkrat; Ukar Tarwiyono; Lina Handayani; Alfrida L S (Jurnal Kimia dan Kemasan, 1998)
The Function of stabilization is to decrease leachate or chemical reaction which is potential to produce pollutant from waste. Three kinds of stabilization such as addition of the cement, lime and organic sludge had been done before. The result showed that the sludge can bind heavy metal. Analysis result showed that the decrease 'in presentation of heavy metal are Zn (79%), Cu (83,5 %), Fe (99,97 %), Mn (JOO %) and Cr (98,2 %). This experiment is continued to find the optimum amount of cement added to the sludge. The result showed that by addition of 5 % cement in textile sludge can hold the heavy metal.